Diagnostic Dilemma of Hepatic Tuberculosis in Presence of Portal Hypertension: A Rare and Relevant Case - Aharbil, F.; Boudda, S.; Errami, A. Ait; Samlani, Z.; Oubaha, S.; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Tuberculosis (TB) is and remains a growing public health problem worldwide, especially in developing countries. Hepatic tuberculosis is an extremely rare form of extra pulmonary TB. Our case report describes hepatic tuberculosis revealed by an atypical sign: portal hypertension (PHT) in a Moroccan immuno competent young man. Case Report: A 28-year-old male with no medical history, was admitted with an abundant ascites, and a chronic right hypochondrium pain. The biology data found a low protein concentration ascitic fluid with signs of portal hypertension in the abdominal ultra sound (US). An abdominal CT scan demonstrated a multi nodular liver with profound multiple lymph nodes some with a necrotic center. The diagnosis of multifocal tuberculosis was clinched on by the positivity of Xpert MTB/RIF assay on sputum and on hepatic needle biopsy. Conclusion: Portal hypertension secondary to hepatic tuberculosis is exceptional and often causes a diagnostic dilemma. It should be considered in the differential diagnosis of non-cirrhotic portal hypertension especially in endemic areas.